Impact of ICON on the Adhesive Microleakage Underneath Orthodontic Bracket (Global Journal of Medical Research, 2023)
Objectives The aims was to assess the changes in tooth orthodontic bracket interface micro-leakage after applying a caries resin penetrated to the sound enamel tooth surface Materials and Methods Sixty human maxillary first premolars were collected randomly separation of the teeth into two groups The experimental one treated with ICON was categorized in to three subgroups n 10 each ICON in distal water ICON in cow milk ICON in Coca cola while control group was classified three subgroups n 10 control in distal water control in cow milk control in Coca Cola incubation time persisted three weeks in total Results A one-way analysis of variance ANOVA produced a significant difference between all experimental groups ICON in distal water ICON in milk ICON in Coca Cola drink and control subgroups control in distal water control in Cow milk Control in Coca Cola
Keywords: caries infiltration; enamel; ICON; microleakage; white spot lesion